Campus security director perceptions concerning the influence of concealed carry firearms on safety at Wyoming public community colleges: a phenomenological study - Hosking, Jeff, author; Foley, Jeffrey M., advisor; Kuk, Linda, committee member; Strathe, Marlene I., committee member; Schaeffer, Steven Lewis, committee member (Colorado State University. Libraries, 2014)
Firearm violence is occurring on America's higher education campuses killing not only students but faculty and employees as well (International Association of Campus Law Enforcement Administrators, 2008). Even in light of this bloodshed, there is little accurate information available about the role that firearms play in preventing or exacerbating campus violence (Miller, Hemenway, & Weschsler, 2002). Wyoming community college campus security directors are specifically given the authority to allow, or not, concealed firearms on their campuses by state law (Wyoming Senate, 2011). The purpose of this qualitative phenomenological study is to explore the perceptions, attitudes, and understandings of campus security directors concerning concealed carry firearms on their campuses. Using qualitative research methods, the study was conducted utilizing semi - structured interviews with the seven campus security directors for each of the Wyoming community college districts. Smith's (2012) interpretative phenomenological analysis qualitative method of inquiry guided the data analysis. In accordance with an interpretative phenomenological approach, data analysis was undertaken to examine for patterns, trends, and themes that emerged from the campus security directors' responses. The analysis used personal and in - depth detail derived from individual interviews to describe the perceptions, attitudes, and understandings of participants. Analysis of the data presented four super ordinate themes supported by fifteen subthemes. This research yielded information concerning the possession of concealed carry firearms at Wyoming community college districts. Findings indicated that the unrestricted carry of concealed firearms would likely harm the overall safety of Wyoming community colleges. However, if proper vetting and training of persons carrying concealed firearms were to occur, campuses may be safer. Wyoming community college districts were considered safe places pursuant to participant responses, and no concealed firearms had been used in any Wyoming community college district to commit a violent crime. Campus security directors stated that possession of firearms by a victim would not have prevented any violent campus crime. Campus security directors indicated that concealed carry firearms may be irrelevant to the safety of Wyoming community college districts. Rather it was the proactive stance and involvement of campus security officers that was important to campus firearm safety. The interview data yielded information and considerations for campus security directors, college administrators and all persons interested in firearm safety at Wyoming community colleges. This information may be used to assist in the crafting of sensible firearm policies at community colleges.
Keywords: concealed; community; firearms; carry; college